2015
DOI: 10.1038/nm.4003
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-δ is repressed in Huntington's disease, is required for normal neuronal function and can be targeted therapeutically

Abstract: Huntington’s disease (HD) is a progressive neurodegenerative disorder caused by a CAG-polyglutamine repeat expansion in the huntingtin (htt) gene. We found that peroxisome proliferator-activated receptor delta (PPARδ) interacts with htt and that mutant htt represses PPARδ-mediated transactivation. Increased PPARδ transactivation ameliorated mitochondrial dysfunction and improved cell survival of HD neurons. Expression of dominant-negative PPARδ in CNS was sufficient to induce motor dysfunction, neurodegenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 58 publications
2
95
0
Order By: Relevance
“…Moreover, Dickey and colleagues recently tested the PPARδ agonist KD3010 in HD N171-82Q transgenic mice. They observed improved motor function, decreased neurodegeneration and longer survival in HD mice [66].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, Dickey and colleagues recently tested the PPARδ agonist KD3010 in HD N171-82Q transgenic mice. They observed improved motor function, decreased neurodegeneration and longer survival in HD mice [66].…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, GPR52 knockdown lowered caspase 3 activity in response to BDNF withdrawal. Moreover, the number of condensed nuclei after BDNF withdrawal was reduced by peroxisome proliferator-activated receptor gamma (PPAR δ ) activator (KD3010) [92]. Many research groups have described drug effect of BDNF or FGF/LIF withdrawal, considered as a stress factor on cell survival [88].…”
Section: Ipscs Providing New Tools For Developing Treatments For Cmentioning
confidence: 99%
“…The importance of PGC-1α for HD pathogenesis is underscored by the observation that PGC-1α overexpression is sufficient to rescue motor dysfunction, prevent accumulation of misfolded htt protein, and stave off neurodegeneration in HD mice (9). To determine the mechanistic basis for PGC-1α transcription interference in HD, we performed an unbiased screen that showed PPARs to be htt interactors, and documented an interaction between PPARδ and htt in non-neuronal cells, in striatal-like neurons, and in the cerebral cortex of HD mice (10). We noted that PPARδ is highly expressed in neurons of the central nervous system (CNS), and demonstrated that expression of dominant-negative PPARδ in CNS is sufficient to produce motor phenotypes, neurodegeneration, mitochondrial defects, and transcriptional abnormalities that closely parallel HD disease phenotypes (10).…”
Section: Introductionmentioning
confidence: 99%
“…To determine the mechanistic basis for PGC-1α transcription interference in HD, we performed an unbiased screen that showed PPARs to be htt interactors, and documented an interaction between PPARδ and htt in non-neuronal cells, in striatal-like neurons, and in the cerebral cortex of HD mice (10). We noted that PPARδ is highly expressed in neurons of the central nervous system (CNS), and demonstrated that expression of dominant-negative PPARδ in CNS is sufficient to produce motor phenotypes, neurodegeneration, mitochondrial defects, and transcriptional abnormalities that closely parallel HD disease phenotypes (10). We then evaluated a selective, potent PPARδ agonist, KD3010, and after confirming that it crosses the blood brain barrier to up-regulate expression of PPARδ target genes in cortex and striatum, we tested KD3010 in N171-82Q transgenic mice, a rodent model of HD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation